A homozygous I684T in GLE1 as a novel cause of arthrogryposis and motor neuron loss. Issue 1 (24th November 2017) - Paakkola, T.; Vuopala, K.; Kokkonen, H.; Ignatius, J.; Valkama, M.; Moilanen, J.S.; Fahiminiya, S.; Majewski, J.; Hinttala, R.; Uusimaa, J.
Abstract : Mutations in GLE1, RNA export mediator ( GLE1 ) gene have previously been shown to cause motor neuron diseases such as lethal congenital contracture syndrome 1 (LCCS1) and lethal arthrogryposis with anterior horn cell disease (LAAHD), including arthrogryposis, fetal akinesis and motor neuron loss as common clinical features. The homozygous FinMajor mutation p.T144_E145insPFQ has been described as one of the causes for LCCS1 whereas LAAHD is caused by a heterocompound FinMajor mutation together with p.R569H, p.V617M or p.I684T missense mutation. None of these heterocompound missense mutations have previously been reported as homozygous states. Here we present the clinical features of 2 siblings with a homozygous p.I684T mutation in GLE1 . The patients suffered from similar, but milder symptoms than in LCCS1 and LAAHD, surviving up to 6 months before they died due to a progressive disease course including respiratory failure. Arthrogryposis, lack of spontaneous movements, and epilepsy were notable in both cases and lack of anterior horn cells was identified in autopsy samples. Our studies on patient‐derived fibroblasts show that the homozygous p.I684T impairs the nuclear localization of GLE1 further confirming the pathogenic role of this mutation. Abstract : GLE1 is found in the nucleus and cytoplasm; however, the majority of the protein localizes in the nuclear pore complex (NPC) where it functions in activating the Dbp5 NPC protein which functions in the transport of mRNA from the nucleus through the NPC into the cytosol. Our data show that the majority of the protein localized in the nucleus in the control fibroblasts. Patient‐derived fibroblasts with the homozygous GLE1 p.I684T did not show as clear localization of GLE1 in the nuclear membrane and the amount of protein was decreased in the nuclei. It is likely that the C‐terminal location of this mutation intervenes with its correct localization in the NPC.